Physical and mechanical properties evaluation of experimental nanohybrid dental composite reinforced with nanosized zirconia and macrosized alumina - Nordin, Nurul Najwa Mohd (2024)
An experimental nanohybrid dental composite (NHDC) using silica extracted from rice husk has been developed. However, the physical properties of NHDC are still inferior as compared to the commercial dental composite. This study aimed to enhance the NHDC properties using nano-sized Zirconia and macro-sized alumina reinforcing fillers, focusing on the physical and mechanical properties of the NHDC. Nanosilica white powder, derived from rice husk, was used as a filler in NHDC. This dental composite was reinforced with nano-sized zirconia (ZrO2) and macro-sized alumina reinforcing fillers (Al2O3), which were divided into three NHDC groups: reinforced with Zirconia (3%) & Alumina (2%), reinforced with Zirconia (2%) & Alumina (3%), and reinforced with Zirconia (3%) only. NHDC with no filler reinforcement and FiltekTM Z250XT were used as a negative and positive control, respectively. The distribution of filler particles inside NHDC was evaluated using FESEM. The NHDCs were then tested for their physical and mechanical properties, respectively. The distribution of filler particles is homogenously distributed, and the surfaces of the experimental NHDCs appeared smooth. The Vickers hardness, surface roughness, flexural strength, and translucency properties showed that zirconia and alumina reinforced NHDC were statistically higher than the control. However, these values are significantly lower than the commercial product FiltekTM Z250XT (p < 0.05). For gel content, the values of all experimental NHDC indicate non-significant difference between no reinforced filler (control group) and Commercial FiltekTM Z250XT, (p > 0.05). Zirconia & Alumina reinforcement also improves the degree of conversion of experimental NHDC compared to the control and commercial product FiltekTM Z250XT (p < 0.05). This study concludes that zirconia and alumina reinforcement improve the properties of the experimental NHDC and could be used as future filler in dental composite reinforcement.